Chloride binding and desorption mechanism in blended cement containing supplementary cementitious materials exposed to de-icing brine solutions - Teymouri Moogooee, Mohammad, author; Atadero, Rebecca, advisor; Fantz, Todd, advisor; Jia, Gaofeng, committee member; Bailey, Travis, committee member (Colorado State University. Libraries, 2024)
Concrete, the most widely used construction material globally, faces significant challenges due to its porous nature, particularly from chloride-induced corrosion. This corrosion, primarily caused by chloride ions penetrating concrete, affects over 7.5% of U.S. concrete bridges, incurring annual costs ranging from $5.9 to $9.7 billion. Chlorides enter concrete from various sources, including de-icing salts. Maritime infrastructures also suffer from severe chloride-induced corrosion because seawater contains a high concentration of chloride ions. Irrespective of how chlorides enter the concrete, chlorides can exist in concrete in two forms: free and bound chlorides. While bound chlorides are beneficial, they can be released due to environmental factors like carbonation and chemical attacks, exacerbating corrosion rates. These attacks cause pH reduction in concrete and subsequently can result in the release of bound chlorides (chloride desorption).This dissertation aims to address three main objectives: (1) investigate factors influencing chloride binding measurements due to lack of a standardized method for chloride binding measurements, (2) study chloride desorption mechanisms in different cementitious systems exposed to de-icing brines, and (3) analyze pH and compositional changes in blended pastes under chloride contamination and carbonation. First, factors impacting chloride binding measurements were identified, such as sample form and saturation level, solution composition, and solution volume. Vacuum-saturated samples exhibited higher chloride binding than partially saturated or dried samples, with powdered samples showing the highest binding. Secondly, chloride desorption mechanisms were investigated in both Ordinary Portland Cement (OPC) pastes and pastes containing supplementary cementitious materials (SCMs) like fly ash, slag, and silica fume. Results indicated that the type of cation in the brine solution influenced bound chloride levels, with SCMs improving chloride binding capacity. Slag inclusion was effective in promoting chloride binding, while silica fume showed the least effect. The degree of chloride desorption under acid attack depended on the acid-to-paste mass ratio. The results reveal that inclusion of fly ash and slag is favorable in terms of chloride desorption, and silica fume is not recommended for use when chloride-induced corrosion is a concern. MgCl2 and CaCl2 de-icers demonstrated a lower chloride desorption compared to NaCl. Finally, the synergistic effects of chloride contamination and carbonation were examined in OPC and fly ash-containing pastes. Carbonation led to over 95% chloride desorption after two weeks, with fly ash-containing pastes exhibiting lower pH levels due to reduced portlandite content. Incorporation of fly ash is not recommended when carbonation is a concern. Therefore, caution should be exercised when considering fly ash inclusion in mixtures where both chloride contamination and carbonation are simultaneous concerns. This dissertation contributes to understanding chloride desorption in cementitious systems, essential for enhancing the durability and service life of concrete structures. This dissertation shed lights on primary factors influencing chloride binding measurements, enhancing the accuracy and comparability of chloride binding results. The results reveal that type of cation present in the solution and type of SCMs have significant influences on the pH, chloride binding capacity, and chloride desorption rates.
Keywords: concrete; de-icers; service life; corrosion; chlroide desorption; pH